English to Arabic translation of the Composite Abuse Scale (CAS): a multi-method approach. - Samia Alhabib; Gene Feder; Jeremy Horwood (PLoS ONE)
Background The composite abuse scale (CAS) is a comprehensive tool used to measure intimate partner violence (IPV). The aim of the present study is to translate the CAS from English to Arabic. Methods The translation of the CAS was conducted in four stages using a multi-method approach: 1) preliminary forward translation, 2) discussion with a panel of bilingual experts, 3) focus groups discussion, and 4) back-translation of the CAS. The discussion included a linguistic validation by a comparison of the Arabic translation with the original English by assessing conceptual and content equivalence. Findings In all the stages of translation, there was an agreement to remove the question from the CAS that asked women about the use of objects in the vagina. Wording, format and order of the items were refined according to comments and suggestions made by the experts' panel and focus groups' members. The back-translated CAS showed similar wording and language of the original English version. Conclusions The Arabic version of the CAS will help to measure the problem of IPV among Saudi women and possibly other Arabic-speaking women in future studies. This is important, particularly, in longitudinal studies or intervention studies among abused women and it allows a comparison of the results of studies from different cultures. However, further validations studies are needed to ensure accurate and equivalent Arabic translation of the CAS.